Status Hukum Pulau-Pulau Buatan Di Laut Lepas Berdasarkan Unclos 1982 Dan Dampaknya Terhadap Penentuan Garis Pangkal - Wahyu Ageng Rizki Dian Pradana; Wendi Ananda Ginting; Haikal Ithar Arami; Aldino Betrach Meky (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Advances in marine reclamation technology have prompted several states to construct artificial islands in high seas areas, particularly in regions subject to jurisdictional disputes. This phenomenon raises fundamental questions in international law, specifically regarding the legal status of such artificial islands and their consequences for baseline determination under the United Nations Convention on the Law of the Sea (UNCLOS) 1982. This article examines two main issues: first, how UNCLOS 1982 regulates the legal status of artificial islands on the high seas; and second, how the presence of artificial islands affects the determination of baselines and a state's maritime boundaries. Through a normative juridical approach with a case study of the South China Sea dispute, this research finds that UNCLOS 1982 explicitly distinguishes between natural islands and artificial islands, whereby artificial islands have no territorial sea of their own and cannot be used as basepoints for baseline determination. The 2016 Permanent Court of Arbitration (PCA) award in the Philippines v. China case reinforces this legal position by affirming that reclamation activities do not alter the original character of a maritime feature.